The Low Level of Digital Literacy in Indonesia: An Analysis of Online Media Content - Afrina, Cut; Zulaikha, Sri Rohyanti; Jumila, Jumila (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2024)
Background of the study: The low level of digital literacy among Indonesians poses a significant challenge in the era of global digitization, particularly due to the lack of access to and understanding of information technology required to make effective use of digital libraries. Purpose: Identify factors causing low digital literacy, evaluate policies that have been implemented, and formulate effective strategies to increase digital library utilization in Indonesia. Method: This study uses a qualitative approach by analyzing online news using the keyword ‘digital literacy’, to explore the factors that lead to low digital literacy in Indonesia. Data analysis methods included coding, theme building, data reduction, and data display to identify patterns and reasons behind this phenomenon. Findings: This research reveals that Indonesia's low digital literacy is caused by a lack of infrastructure, a lack of educational focus, and low awareness of social media ethics. Collaboration between the government, academic institutions, and society is needed through technology investment, education reform, and awareness campaigns. Conclusion: Recommended follow-up includes training, digital infrastructure development, and effective awareness campaigns to improve digital literacy in Indonesia.